Renewal Of Arabic Grammar (Nahw) By Al-Shatibi In Al Maqashid Al Syafiyah - Nurdianto, Talqis; Ritonga, Mahyudin (Ijaz Arabi Journal of Arabic Learning, 2021)
Learning Arabic to non-Arabic makes nahw (Arabic syntax) an important part that cannot be overlooked. The formulation of nahw renewal occurred in line with differences of opinion from previous scholars. As nahw developed as a science, its discussion became more complex and obscure. The emergence of the Basran and Kufan schools drove fanaticism among scholars, and their debates revolved around increasingly complex topics. While these discourses expanded the knowledge body of nahw, those grammarians did not propose anything novel, and its topics soon became incomprehensible to non-Arab learners. There was, therefore, a great urgency to reform and simplify nahw for such learners. Within this context, this study attempts to examine the innovative methods introduced by al-Shatibi to simplify and rejuvenate nahw through his book al-Maqashid al-Shafiah fi Sharh al-Khulashah al-Kafiah. To achieve this objective, data were obtained through library research, primarily from Al-Shatibi's text and other related sources. The findings revealed that Al-Shatibi's diverse educational background allowed him to elucidate the principles through simple, straightforward sentences. His method in al-Maqashid was distinctive: He cited all the differing opinions in a given problem, supporting some while criticizing the others; his deep understanding of Alfiyah allowed him to clarify its implicit meanings; his excellence in fiqh and other sciences manifested in his commentary of some nahw problems; and he employed exemplary expressions in his writings, such as explicitly selecting a rule or opinion and not being vague, stating his preferred opinions, and implicitly deciding on an opinion. Al-Shatibi's educational approach, employing questions and answers, hypothetical arguments and counters, and systematic organization allowed non-Arabs to benefit significantly from the book.